FRAMING HAMAS: A COMPARATIVE DISCOURSE ANALYSIS OF WESTERN AND MIDDLE EASTERN MEDIA - Henarni, Nabila Humairo; Surwandono, Surwandono (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2024)
After the 9/11 attacks, Western society, especially the United States, began to consider Islam as a religion that gave birth to terrorist organizations. Many media also brand organizations related to the Islamic religion as terrorists, including Hamas. In order to emphasize the intricate relationships between media, geopolitics, and the formation of public opinion, this research seeks to analyze potential biases and contrasting narratives between Western and Middle Eastern opinions on Hamas. In order to examine depictions of Hamas as a